How platforms are transforming customer information management. Issue 3 (13th November 2017) - Stone, Merlin; Aravopoulou, Eleni; Gerardi, Gherardo; Todeva, Emanuela; Weinzierl, Luisa; Laughlin, Paul; Stott, Ryan
Abstract : Purpose: The purpose of this paper is to explain how ecosystems and platforms have evolved to manage customer information and to identify the management, research and teaching implications of this evolution. Design/methodology/approach: This paper is based on research and industrial experience of two of the co-authors in customer relationship management, further developed with other co-authors in the field of business models, the research and teaching experience of the university authors and cross-functional literature reviews in the areas of strategy, marketing, economics, organizational behaviour and information management. Findings: This paper shows that digitalization, cloud computing and new information-based platforms are beginning to change how customer information is being managed, creating new opportunities for improving marketing, customer relationship management and business strategy. Research limitations/implications: The impact of platforms on the management of customer information needs to be confirmed by primary empirical research. Practical implications: This paper identifies the need for senior marketing management to examine closely how internal and external/public customer information platforms may enhance their capability for managing customers and setting new strategic directions. Social implications: The emergence of giant multi-sided platforms has clear implications for data protection and privacy, which need to be explored more in research. Originality/value: This paper highlights the move to customer information platforms and identifies how senior managers should consider them as an option for better customer information management and as a basis for new business strategies.